Isotretinoin Therapy and Physical Activity - Implications for Athletes and Physically Active Individuals - Herc, Bartosz Przemysław; Tesla, Małgorzata; Gąska, Anna Agnieszka; Gutkowska, Marta; Jabłońska, Joanna; Wasik, Joanna; Armuła, Marta; Bongage, Claire; Piechowiak, Arkadiusz; Napieraj, Filip (Quality in Sport, 2026)
Background. Isotretinoin is widely used and highly effective in the treatment of severe acne. However, its use is associated with a broad range of adverse effects, some of which may be particularly relevant in physically active individuals. Athletes are often exposed to factors that increase the risk of acne and may therefore be more likely to require systemic treatment. At the same time, the potential impact of isotretinoin on physical performance and training remains unclear. Aim. The aim of this narrative review was to summarise the current knowledge on the adverse effects of isotretinoin, with a focus on those that may be important in physically active individuals. Material and methods. A literature search was performed using PubMed and Web of Science databases, including studies published between 2016 and 2026. The search included terms related to isotretinoin, physical activity, exercise, and adverse effects. Only articles published in English were considered, and the results were reviewed and organised thematically. Results. The findings suggest that isotretinoin may affect several organ systems. Musculoskeletal symptoms, such as muscle and joint pain or increased creatine kinase levels, seem particularly relevant in individuals who engage in regular physical activity. Ocular and mucocutaneous side effects, although usually mild, may still influence comfort during exercise. The relationship between isotretinoin and mental health appears more complex, with most studies indicating a low overall risk, but some patients still reporting mood-related symptoms. Conclusions. While isotretinoin is an effective treatment, its effects are not limited to the skin and may be more noticeable in physically active individuals. In this group, even mild side effects can affect training and overall well-being. At the same time, there is still a lack of research focused specifically on athletes, which highlights the need for further studies in this area.